2013
DOI: 10.1001/jamaneurol.2013.1956
|View full text |Cite
|
Sign up to set email alerts
|

Autosomal Dominant Spastic Paraplegias

Abstract: Importance: Hereditary spastic paraplegias (HSPs) are a group of diseases caused by corticospinal tract degeneration. Mutations in 3 genes (SPG4, SPG3, and SPG31) are said to be the cause in half of the autosomal dominant HSPs (AD-HSPs). This study is a systematic review of families with HSP resulting from a population-based survey. Novel genotype-phenotype correlations were established. Objective: To describe the clinical, genetic, and epidemiological features of Portuguese AD-HSP families. Design: Retrospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(18 citation statements)
references
References 53 publications
1
15
0
2
Order By: Relevance
“…In addition, R239C ( n  = 31) [6, 9, 11, 13, 15, 17, 21, 22, 2729, 31, 32, 36, 39, 45, 51, 53, 54, 56] and R495W ( n  = 14) [1517, 21, 32, 36, 43, 50, 52, 54] mutations were the most commonly reported mutations in all studied families. Zhao et al reported that the three families with R239C mutations were not apparently related and haplotype analysis did not exclude a distant founder effect [6].…”
Section: Discussionmentioning
confidence: 97%
“…In addition, R239C ( n  = 31) [6, 9, 11, 13, 15, 17, 21, 22, 2729, 31, 32, 36, 39, 45, 51, 53, 54, 56] and R495W ( n  = 14) [1517, 21, 32, 36, 43, 50, 52, 54] mutations were the most commonly reported mutations in all studied families. Zhao et al reported that the three families with R239C mutations were not apparently related and haplotype analysis did not exclude a distant founder effect [6].…”
Section: Discussionmentioning
confidence: 97%
“…As in previously published population-based studies, SPG4 and SPG3A were the most frequent AD-HSP. 15,20,21 SPG4 accounts for up to 45% of AD-HSP and up to 20% of sporadic cases, 22 while SPG3A accounts for nearly 10% of AD-HSP. 18 SPG8 was present in 5% of our cohort, which is more common compared to previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…20,26,27 This is likely due to very recent advances in genetic diagnoses of HSP compared to the common SCAs and highlights the need for good natural history data to identify parameters which influence clinical outcomes of HSP. 28 There is one study which examined the correlation between disease duration and spasticity in patients with HSP, but unfortunately, the genetic diagnoses were not reported.…”
Section: Discussionmentioning
confidence: 99%
“…SPG11 and SPG15 are the two major loci for this entity, comprising more than 40% of cases, while SPG21/ACP33 (maspardin), SPG44 (GJC2), SPG49/56 (CYP2U1), SPG46 (GBA2), SPG47 (AP4B1), SPG54 (DDHD2), and SPG63 (AMPD2) are less frequent [5,21]. Truncating mutations in the ZFYVE26 gene leading to loss of function of spastizin cause SPG15 and Kjellin's syndrome characterized by central retinal degeneration in addition to TCC, and similar clinical and imaging presentations to SPG11 with TCC and WM hyperintensities in MRI [13,14,27,28].…”
Section: Discussionmentioning
confidence: 99%
“…There are currently 76 different HSP, and 59 of them have been identified according to their genotypic classification by mapped genetic loci or mutated genes so far, with that number steadily increasing [4]. The most common AD-HSP are SPG4, SPG3A, and SPG31, caused by mutations in the genes spastin , atlastin , and REEP1, respectively, and account for more than 50% of AD-HSP [3,4,5]. Among the most common AR-HSP are SPG11 and SPG5, depending on the population [3,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20].…”
Section: Introductionmentioning
confidence: 99%